7 - Enforcement of Intellectual Property Rights – Blessing or Curse? A Perspective from Mauritius - Goburdhun, Kaushik (Africa Development, 2007)
The Mauritian economy is facing serious economic difficulties, and the govern- ment is being pressurised to maintain the competitive edge of various industries by giving a panoply of incentives, including laws and institutions that can effectively protect intellectual property rights, to the business community, both local and foreign. This paper examines the issues of intellectual property rights in Mauritius by first surveying the main economic challenges of Mauritius, particularly the need for increased foreign investment to maintain growth, and then by discussing the various intellectual property laws enacted since the adhesion of Mauritius to the World Trade Organisation (WTO). It examines the harsh response of the law enforcement institutions and the heavy price that weaker and more vulnerable people have had to pay and queries whether Mau- ritius implemented the Trade Related Aspects of Intellectual Property Rights agreement mainly in order to benefit from the African Growth and Opportunity Act. The paper argues that, while the enforcement of intellectual property rights may send a positive signal to potential investors, it may also make it harder for weaker segments of the population to sustain a decent livelihood. It is proposed that the law may have to be changed to allow courts to take into account the social circumstances of a person breaching the provisions of intellectual prop- erty legislation. The role of the courts should not simply be one of inflicting punishment; they should also be capable of fostering a sense of responsibility and accountability on the part of offenders.